Characteristics of outpatient gynecology oncology services before and after COVID-19 pandemic at Ulin Regional General Hospital, Banjarmasin, Indonesia - Setyo Teguh Waluyo; Ferry Armanza; Hariadi Yuseran; Kevin Stanley Halim (Universitas Airlangga, 2023)
HIGHLIGHTS The characteristics of gynecology oncology services at Ulin Regional General Hospital before and after the COVID-19 pandemic were evaluated. There was a decrease of 19% in the number of visits by Gynecology Oncology Clinic patients at Ulin Regional General Hospital between the period of March 2019 - February 2020 and March 2020 - February 2021. ABSTRACT Objective: The aim of this study was to investigate the characteristics of the Gynecology Oncology Outpatient Clinic at Ulin Hospital Banjarmasin before and after the COVID-19 pandemic. Materials and Methods: This descriptive study utilized existing patient data from the Gynecology Oncology Outpatient Clinic at Ulin Hospital Banjarmasin covering the period from March 2019 to February 2021. The study received ethical approval from the Ulin General Hospital ethics committee with clearance number 10/I-Reg Research/RSUDU/23. The collected data was presented in a tabular format to compare the service characteristics before the pandemic (March 2019 - February 2020) and after the pandemic (March 2020 – February 2021). Results: During the periods of March 2019 – February 2020 and March 2020 – February 2021, there was a reduction of 19% in patient visits. The number of patients undergoing treatment also decreased, from 1081 patients (53.9%) in the period of March 2019 – February 2020 to 926 patients (46.1%) in the period of March 2020 – February 2021. Notably, there was a decrease in the number of patients undergoing surgical procedures, dropping from 76 patients (70.4%) in the period of March 2019 – February 2020 to 32 patients (29.6%) in the period of March 2020 – February 2021. A similar trend was seen in patients receiving chemotherapy, with the count decreasing from 1005 patients (52.9%) in the period of March 2019 – February 2020 to 894 patients (47.1%) in the period of March 2020 – February 2021. These changes were attributed to various hospital measures implemented to address the COVID-19 pandemic, including a reduction in outpatient clinic visits and the temporary suspension of surgical procedures from March 2020 to October 2020 to minimize potential exposure. Conclusion: The study highlights a noticeable decline in both the frequency of visits to the Gynecology Oncology Outpatient Clinic at Ulin Regional General Hospital Banjarmasin and the number of patients receiving treatment during the periods before and after the onset of the COVID-19 pandemic.